A sociological explanation of the comparison of debate rules in both Koranic verses and poems by poets - Janmardi, Mahvash (IJRDO - Journal of Social Science and Humanities Research, 2018)
Debate is a purposive and systematic discussion to understand opinions and is founded on question and answer criticism methodology. Viewing the significance and role of debate in economic social, political and cultural development of the society, the present article sought to compare debate rules via utilizing document methods and reviewing Koranic verses and poems by poets. According to the research findings, such issues as seeking truth, applying sciences, reasoning, eloquent expression, tolerance, avoiding prejudice, insightfulness and respect are thought of the most important rules for debate as invoked by the Koranic verses. Meantime, the chapters in the holy book such as A'raf, Fath, Forghan, Asra', Haj, Loghman, Ghafer, Nahl, Ankaboot, and the debate between angles and God, the almighty, God, the almighty and the Satan, Prophet Abraham (peace be upon him) and Nimrod, idolatrous, star worshipping people, and prophet Saleh and his tribe in the Koran all suggest a strong confirmation over systematic observance of debates. The literary expression by such poets as Ferdowsi, Asadi Toosi, Nezami, Molavi, Sa'di, Hafez, Bahar, and Parvin E'tesami in the debate technique all suggests some common grounds between poets and Koranic verses